DEVELOPMENT OF PROBLEM CHILDREN THROUGH THE GAPURA PANCA WALUYA PROGRAM FROM THE PERSPECTIVE OF CHILDREN'S RIGHTS PROTECTION - Rizqie Achmad Alfarezi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Gapura Panca Waluya program, initiated by the Governor of West Java through Circular Letter Number 45/PK.03.03/KESRA, is a policy for fostering troubled children through a semi-military approach involving cooperation with the Indonesian Army. This policy has drawn serious attention considering that the categorization of "problem children" in the circular does not clearly differentiate between children who commit juvenile delinquency and children involved in criminal acts. This study aims to analyze the suitability of the Gapura Panca Waluya program with the principle of the best interests of children as well as the criminal accountability of children who have participated in the program. The research method applied is normative law with a legislative approach and is also based on concepts. The research findings reveal that this program is not in line with the principle of the best interests of children as mandated by Law No. 35 of 2014 concerning Child Protection and has the potential to violate children's rights guaranteed in Article 28B paragraph (2) of the 1945 Constitution of the Republic of Indonesia . In addition, this program has the potential to create uncertainty regarding the legal status of children involved in criminal acts, considering that Law No. 11 of 2012 concerning the Juvenile Criminal Justice System already manages a special handling mechanism that should be taken for children in conflict with the law. As a solution, this program can be integrated as a form of diversion agreement for children involved in criminal acts according to the Juvenile Criminal Justice System mechanism.